Patch Testing During Immunosuppressive Therapy: A Systematic Review. Issue 6 (November 2021) - Mufti, Asfandyar; Lu, Justin D.; Sachdeva, Muskaan; Zaaroura, Hiba; Kashetsky, Nadia; Yeung, Jensen; Maibach, Howard I.; DeKoven, Joel
Abstract : Abstract: Patch testing, used in the assessment of allergic contact dermatitis, is ideally avoided in patients receiving immunosuppressive therapy because of concerns with reductions in accuracy; however, this is not well characterized in the literature. This systematic review summarizes patch testing results in patients receiving immunosuppressive therapy. We identified 16 studies, comprising 195 patients with dermatitis or psoriasis, who were patch tested while receiving immunosuppressants. Of these, 7 studies, comprising 85 patients with dermatitis, patch tests were performed before and during immunosuppression. Overall, 67.9% (n = 19) of the dermatitis patients receiving dupilumab maintained positive reactions to an allergen that previously graded as a 2+/3+ reaction. Several immunosuppressants were also associated with positive patch test results for various allergens. These include dupilumab, cyclosporine, and low-dose prednisone (⩽10 mg/d) for dermatitis, and tumor necrosis factor α inhibitors, ustekinumab, and methotrexate for psoriasis. Ideally, it is preferable to patch test when patients are not receiving oral immunosuppressants or immunomodulators. However, clinicians may choose to assess the risks and benefits of patch testing for each patient given the impact of allergic contact dermatitis on patient quality of life.